The relationship between teaching style, self-efficacy and competency in vocational special education teachers - Rubashini Ramakrishnan,; Aliza Alias,; Norshidah Mohd Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this study is to identify and examine the relationship between teaching style, self-efficacy and teacher’s competency in vocational special education secondary schools in Malaysia. Three instruments were used in the study which are Grasha Teaching Style, Teacher Sense of Efficacy Scale (TSES), and Standard Kualiti Pendidikan Malaysia Gelombang 2 (SKPMg2). The study involved a total of 229 teachers and Partial Least Square Structural Equation Modeling (PLS-SEM) was applied for the data analysis. The results found that the teaching style has a positive relationship with teacher’s self-efficacy. Similarly, self-efficacy has a positive relationship with teacher’s competency. Besides that, it was found that self-efficacy is a full mediator of the relationship between teaching style and competency (β = 0.222, p < 0.05). The findings summarised that a positive teaching style will enhance teacher’s self-efficacy and the teachers are more confident in using a variety of teaching styles. Besides, the study also found that self-efficacy is a factor that helps teachers to be more competent in their teaching profession. In fact, the finding obtained self-efficacy as a factor in improving teachers’ positive attitude in teaching and learning process. Moreover, the findings found that teaching style and self-efficacy are among the factors that cultivate the nature of teacher’s competence in terms of knowledge, understanding and skills. In conclusion, studies focusing on teaching style, self -efficacy and competency among special education teachers in integration schools are encouraged in the future.